(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
By the interaction of 1-heptylthio-3-chlor-2-propanol with o-chlor-2-propanol with o-chlorphenoxy in alkaline medium has been synthesized 1- heptylthio-3-(o-chlorphenoxy)-2-chlorpropanol on the base of which received their carbamates, thiocarbamates, acyl-, alcocsimethyl- and aminomethyl derivatives. Synthesized compounds were investigated as anticorrosive and antibacterial additives for lubricant oils.